2021
DOI: 10.3390/jcm10173988
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric History and Overactive Bladder Symptom Severity in Ambulatory Urogynecological Patients

Abstract: Introduction and hypothesis: A link between psychiatric comorbidities and overactive bladder symptomatology has been suggested by preclinical and clinical studies. Given this, we hypothesized that a psychiatric history and current treatment with psychotropic medications could be related to the severity of overactive bladder and incontinence symptoms in patients referred to a tertiary care urogynecological center. Methods: One hundred and twenty-seven female patients diagnosed with an overactive bladder were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Notably, there is evidence suggesting a link between overactive bladder and psychiatric disorders such as depression and anxiety [ 170 , 171 ]. A national cohort study conducted in Taiwan demonstrated significantly higher risk of depression and anxiety in patients with overactive bladder compared to those without overactive bladder [ 172 ].…”
Section: Bladder Microbiotamentioning
confidence: 99%
“…Notably, there is evidence suggesting a link between overactive bladder and psychiatric disorders such as depression and anxiety [ 170 , 171 ]. A national cohort study conducted in Taiwan demonstrated significantly higher risk of depression and anxiety in patients with overactive bladder compared to those without overactive bladder [ 172 ].…”
Section: Bladder Microbiotamentioning
confidence: 99%